A novel real-time DIC-FPGA-based measurement method for dynamic testing of light and flexible structures. (18th March 2019) - Kumar, D; Kamle, S; Mohite, P M; Kamath, G M
Abstract: A high-speed 3D digital image correlation (DIC) setup is developed and coupled with an FPGA-based real-time operating system (RT-FPGA) for dynamic testing of light and flexible structures. An in-house image correlation program is developed using MATLAB. This program is validated using a virtual stereovision system created in AUTODESK 3DS MAX to simulate a translating and rotating plate and generate synthetic images. An experimental setup is designed and fabricated to mount the high-speed cameras at precise relative locations and orientations. The developed 3D-DIC technique is validated by comparing it with a laser displacement sensor while measuring point displacement of a rotating plate mounted on a servo mechanism. The displacement measurements obtained from the DIC setup match those obtained from the laser sensor with less than 2% error. The high-speed cameras are coupled and synchronized with an accelerometer and displacement sensor using the RT-FPGA system. A LabVIEW-FPGA program is developed for the coupling, synchronization and data acquisition tasks. The DIC-FPGA coupling is validated by measuring the oscillatory motion of a rigid block and structural dynamic parameters of an ASTM-standard beam. This technique is successfully applied for structural dynamic testing of a hyperviscoelastic membrane, a polymeric sandwich beam and a biomimetic flapping wing. The present study successfully demonstrates the development, validation and application of a novel real-time high-speed non-contact DIC-FPGA technique. Using the reported validation and application exercises, similar measurement methodology can be developed at any lab and used for dynamic testing of light and flexible structures.